O przyspieszonych procesach cyfryzacji i robotyzacji we współczesnym nieprzewidywalnym świecie – teoria i praktyka - Puślecki, Zdzisław W. (Humaniora. Czasopismo Internetowe, 2023)
The aim of this study is to present the accelerated processes of digitization and robotization in the contemporary unpredictable world from a theoretical and practical perspective. In the new developmental conditions, there has been a radical limitation of social and economic activity and the emergence of new barriers, which has led to an increase in the importance of innovative products and services based on modern technologies, aimed at overcoming the economic and social effects of the COVID-19 pandemic. The goal of some countries was to develop small and medium-sized enterprises (SMEs) to become leaders in the progress of information and communication technologies. During the pandemic, an innovative approach to company development was necessary. Entities supporting entrepreneurs saw great potential in startups, widespread digitization, and actions consistent with sustainable development. The acceleration of the digitization proces influenced long-term organizational changes in enterprises, including more frequent remote work of some employees and the associated reduction in office space rental costs. Uncertainty in the global economy caused by the pandemic prompted many companies to re-evaluate their business models. Instead of relying on global supply chains, more and more companies invested in robots, leading to a renaissance of manufacturing in industrialized countries.